Dynamic voltage restorer under different grid operating conditions for power quality enhancement with the deployment of a PI controller using gorilla troops algorithm - Muhyaddin Rawa; Hadeer N. Mohamed; Yusuf Al-Turki; Khaled Sedraoui; Ahmed M. Ibrahim (Ain Shams Engineering Journal, 2023)
Incorporating renewable energy sources (RESs) into the grid influences the system’s power quality (PQ). These sources are unreliable because of their intermittence. To analyze the influence of RESs like PV and wind farm systems on voltage quality and harmonic analysis, a Dynamic Voltage Restorer (DVR) series compensator is one of the most effective alternatives presently offered. In this work, the DVR is employed to enhance the PQ issues related to the RESs (e.g., voltage sag, swell, flickering, and harmonics). The DVR is controlled by the PI controller with the employment of the gorilla troops algorithm (GTA) to get the gain values of the presented controller under a variety of PQ issues. Two operating modes are addressed – the off-grid mode and the on-grid mode with considerable PV, wind, and nonlinear loads. Moreover, two comparative study evaluations of different optimization strategies and an additional controller are provided to accomplish the desired result and power of the offered DVR. The MATLAB/Simulink platform is used in this study to validate the suggested strategy’s efficiency in various situations. The findings show that the suggested control technique performs well in terms of voltage quality response and harmonic rejection when subjected to grid voltage distortions.